2016
DOI: 10.1016/j.addbeh.2016.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress symptom severity and cognitive-based smoking processes among trauma-exposed treatment-seeking smokers: The role of perceived stress

Abstract: Trauma exposure and smoking co-occur at an alarmingly high rate. However, there is little understanding of the mechanisms underlying this clinically significant relation. The present study examined perceived stress as an explanatory mechanism linking posttraumatic stress symptom severity and smoking-specific avoidance/inflexibility, perceived barriers to smoking cessation, and negative affect reduction/negative reinforcement expectancies from smoking among trauma-exposed smokers. Participants were trauma-expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…For example, extant work indicates that ethnicity may play a moderating role in smoking lapse, with white smokers without PTSD lapsing at a significantly slower rate (i.e., longer time to lapse) than white smokers with PTSD and black smokers with and without PTSD (Wilson et al, 2014). Other work has highlighted perceived stress (Garey et al, 2016), abstinence self-efficacy , and emotional reactivity (Calhoun, Dennis, & Beckham, 2007) as influential to longevity and success of quitting attempts among individuals with PTSD. Further, Dedert et al (2012) found that smokers with PTSD endorsed greater cravings, more withdrawal symptoms, and increased negative affect following overnight abstinence, highlighting negative reinforcement motives as another potential mediator to failed smoking cessations.…”
Section: Cessation-related Protective Factors and Underlying Mechanismsmentioning
confidence: 99%
“…For example, extant work indicates that ethnicity may play a moderating role in smoking lapse, with white smokers without PTSD lapsing at a significantly slower rate (i.e., longer time to lapse) than white smokers with PTSD and black smokers with and without PTSD (Wilson et al, 2014). Other work has highlighted perceived stress (Garey et al, 2016), abstinence self-efficacy , and emotional reactivity (Calhoun, Dennis, & Beckham, 2007) as influential to longevity and success of quitting attempts among individuals with PTSD. Further, Dedert et al (2012) found that smokers with PTSD endorsed greater cravings, more withdrawal symptoms, and increased negative affect following overnight abstinence, highlighting negative reinforcement motives as another potential mediator to failed smoking cessations.…”
Section: Cessation-related Protective Factors and Underlying Mechanismsmentioning
confidence: 99%
“…11 Drawing from self-regulation and coping theories for tobacco use, 12,13 trauma-exposed smokers with higher levels of perceived stress may expect that smoking will lessen their experiential discomfort. Indeed, empirical evidence supports this theoretical model 5 . Thus, robust theoretical and empirical data demonstrate an effect of perceived stress on increased negative reduction smoking expectancies among trauma-exposed smokers.…”
mentioning
confidence: 71%
“…While past work has provided evidence for trauma-related symptoms and perceived stress 5 and perceived stress and negative affect reduction expectancies for smoking 9 separately, the current study broadens this corpus of work by jointly examining the sequential path from trauma-related symptom severity to perceived stress to negative affect reduction expectancies for smoking, and finally to smoking. Thus, this initial work elucidates a conceptual and empirically supported pathway that explains, in part, the relation between trauma-related symptoms and maladaptive smoking behavior and cognition.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations